2015
DOI: 10.35590/jeb.v2i2.716
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Produk Dan Harga Terhadap Loyalitas Melalui Kepuasan Pelanggan Bolt

Abstract: This study was conducted to examine the magnitude of the contribution proposed by the coefficient lines at each track diagram of causal relationships between variables

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
6
1
2
Order By: Relevance
“…Thus, it can be concluded that product quality and price simultaneously have a significant effect on customer loyalty for soft drink products Bubble'ku Bubble Drink and Ice Blend at Ramayana Department Store of Sukabumi City. This is in accordance with the results of previous research conducted by Susilowati & Handayani (2015) and Bulan (2016).…”
Section: The Effect Of Product Quality and Price On Customer Loyaltysupporting
confidence: 94%
“…Thus, it can be concluded that product quality and price simultaneously have a significant effect on customer loyalty for soft drink products Bubble'ku Bubble Drink and Ice Blend at Ramayana Department Store of Sukabumi City. This is in accordance with the results of previous research conducted by Susilowati & Handayani (2015) and Bulan (2016).…”
Section: The Effect Of Product Quality and Price On Customer Loyaltysupporting
confidence: 94%
“…Research conducted by (Septina Dwi Mayasari, 2015) with the results of his research shows that product quality and price affect customer loyalty and customer satisfaction. Likewise, research conducted by (Caesar Andreas, 2006) with the results of his research showing that product quality has a significant and positive effect on customer satisfaction and customer loyalty.…”
Section: Relations Between Variables Service Quality On Customer Sati...mentioning
confidence: 98%
“…To meet customer satisfaction, the company provides good product quality, good service to be able to retain customers and affordable prices. Research conducted by (Septina Dwi Mayasari, 2015) with the results of his research shows that product quality and price affect customer loyalty and customer satisfaction. However, it is different from the research conducted by Fitriani, (2016), found that price, product quality, and service quality do not affect consumer satisfaction.…”
Section: Introductionmentioning
confidence: 98%
“…Consumers will compare expectations before buying a product with what they get after buying the product [37]. This is reinforced by research conducted by Kusmawati (2017) that product quality affects consumer buying interest [38]. The results of the influence of the regression studied showed that product quality had a significant effect on consumer satisfaction.…”
Section: Relationship Between Variablesmentioning
confidence: 99%